CHARACTER DEVELOPMENT IN ELEMENTARY SCHOOL LEARNING FROM A PHILOSOPHY OF SCIENCE PERSPECTIVE - Yusuf Tri Herlambang; Ai Sutini; rohaetul (SOSIOEDUKASI, 2026)
Character development at the elementary school level has become an increasingly urgent issue due to growing moral challenges arising from social change and the expansion of digital technology. Empirical findings indicate that character education practices in elementary schools remain largely normative and have not yet fully supported deep value internalization among students. This study aims to examine character development in elementary school learning through a philosophy of science perspective, encompassing ontological, epistemological, and axiological dimensions. The research employed a Systematic Literature Review using PRISMA guidelines, analyzing 22 relevant scholarly articles published between 2021 and 2025. The findings reveal that integrating the philosophy of science into elementary learning provides a strong conceptual foundation for character education, where values are not merely introduced as rules but are understood, interpreted, and practiced through reflective and contextual learning experiences. In conclusion, the philosophy of science perspective can function as a comprehensive pedagogical framework for character development in elementary school students.